COVID‐19: Thrombosis, thromboinflammation, and anticoagulation considerations. (20th July 2021) - Levy, Jerrold H.; Iba, Toshiaki; Olson, Lyra B.; Corey, Kristen M.; Ghadimi, Kamrouz; Connors, Jean M.
Abstract: Vascular endothelial injury is a hallmark of acute infection at both the microvascular and macrovascular levels. The hallmark of SARS‐CoV‐2 infection is the current COVID‐19 clinical sequelae of the pathophysiologic responses of hypercoagulability and thromboinflammation associated with acute infection. The acute lung injury that initially occurs in COVID‐19 results from vascular and endothelial damage from viral injury and pathophysiologic responses that produce the COVID‐19–associated coagulopathy. Clinicians should continue to focus on the vascular endothelial injury that occurs and evaluate potential therapeutic interventions that may benefit those with new infections during the current pandemic as they may also be of benefit for future pathogens that generate similar thromboinflammatory responses. The current Accelerating COVID‐19 Therapeutic Interventions and Vaccines (ACTIV) studies are important projects that will further define our management strategies. At the time of writing this report, two mRNA vaccines are now being distributed and will hopefully have a major impact on slowing the global spread and subsequent thromboinflammatory injury we see clinically in critically ill patients.